THE INFLUENCE OF PHYSICAL ACTIVITY ON THE PHYSICAL DEVELOPMENT OF SCHOOLCHILDREN - Nurullaev Yo.E., Kamilova R.T., Slavinskaya N.S. (Central Asian Journal of Medicine, 2025)
Research has shown that physical activity in school-age children has a positive impact on their physical development, particularly during adolescence. Girls aged 11-15 who participate in sports exhibit significantly higher body mass and height measurements compared to their inactive peers. For boys, the most pronounced effects of physical activity are seen in height measurements during the early school years (ages 7-10), indicating that physical activity is especially important for stimulating linear growth in the early stages of school age. It has been established that regular physical exercise contributes to accelerated somatic development during puberty.